Pengaruh Kecerdasan Emosional terhadap Kinerja Karyawan - Pratama, Aditya Yuda; Suhaeni, Tintin (Jurnal Riset Bisnis dan Investasi, 2017)
Culinary business from every new is always increasing, has always been the highest compared with other types of business. Based on data from the print media, Bandung is designated as an Indonesian culinary destination because it contributes greatly to the state revenue. However, there are problems that often occur especially in the culinary field, one of which is from human resources. This study was conducted to determine the effect of human resources viewed from emotional intelligence to employee performance. The method used is descriptive analysis to obtain the results of emotional intelligence is in the high category and employee performance is also in the high category. The result of simple linear regression analysis obtained equation Y = 13.060 + 0.420X, with R Square of 0.599 means there is contribution between emotional intelligence to employee performance equal to 59.9%.